The pelleting of clovers and fertiliser : the effects of the localized placement of fertiliser at seeding (pelleting) on germination, morphology and herbage yield of Trifolium species : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science to the University of New Zealand [Massey Agricultural College] - Smith, C. A (Massey Agricultural College, 1951)
The pelleting of clover seed and fertiliser may be valuable as a method of introducing the essential clovers into the unploughable hill country. The hill land of New Zealand is agriculturally important because of the large area involved, the animals and animal products produced and its value as a souce of direct and indirect employment. The hill country indirectly influences the valuable lowlands. There are two aspects: firstly, the supply of store stock for fattening and breeding (which results in a continuous transfer of minerals as animal skeletons); and secondly the importance of the hill catchment areas in the prevention of flood discharges, and the silting of rivrs, flats and resevoirs lower down.
Keywords: Pelletized seeds; Clover